Sensory processing of deep tissue nociception in the rat spinal cord and thalamic ventrobasal complex. Issue 14 (18th July 2017) - Sikandar, Shafaq; West, Steven J.; McMahon, Stephen B.; Bennett, David L.; Dickenson, Anthony H.
Abstract: Sensory processing of deep somatic tissue constitutes an important component of the nociceptive system, yet associated central processing pathways remain poorly understood. Here, we provide a novel electrophysiological characterization and immunohistochemical analysis of neural activation in the lateral spinal nucleus (LSN). These neurons show evoked activity to deep, but not cutaneous, stimulation. The evoked responses of neurons in the LSN can be sensitized to somatosensory stimulation following intramuscular hypertonic saline, an acute model of muscle pain, suggesting this is an important spinal relay site for the processing of deep tissue nociceptive inputs. Neurons of the thalamic ventrobasal complex (VBC) mediate both cutaneous and deep tissue sensory processing, but in contrast to the lateral spinal nucleus our electrophysiological studies do not suggest the existence of a subgroup of cells that selectively process deep tissue inputs. The sensitization of polymodal and thermospecific VBC neurons to mechanical somatosensory stimulation following acute muscle stimulation with hypertonic saline suggests differential roles of thalamic subpopulations in mediating cutaneous and deep tissue nociception in pathological states. Overall, our studies at both the spinal (lateral spinal nucleus) and supraspinal (thalamic ventrobasal complex) levels suggest a convergence of cutaneous and deep somatosensory inputs onto spinothalamic pathways, which are unmasked by activation of muscle nociceptive afferents to produce consequent phenotypic alterations in spinal and thalamic neural coding of somatosensory stimulation. A better understanding of the sensory pathways involved in deep tissue nociception, as well as the degree of labeled line and convergent pathways for cutaneous and deep somatosensory inputs, is fundamental to developing targeted analgesic therapies for deep pain syndromes. Abstract : Our study explores the central nervous system processing of deep tissue nociceptive inputs. We use electrophysiology and immunohistochemistry in rats to provide a novel characterization of the lateral spinal nucleus and its role in somatosensory processing of acute and pathological muscle activation. We also characterize the evoked activity of neurons in the thalamic ventrobasal complex and demonstrate sensitization of subpopulations of these neurons to mechanical somatosensory stimulation following muscle stimulation with hypertonic saline.